Effects of the early period of the COVID-19 pandemic on psoriatic disease severity and treatment - Fatma Nalbant; Ekin Şavk; Meltem Uslu; Münevver Güven (Galenos Publishing House, 2023)
Background and Design: The coronavirus disease-2019 (COVID-19) pandemic caused unexpected and drastic changes in the modus operandi of global healthcare. Psoriasis is a dermatosis that necessitates the provision of special healthcare services in dermatology clinics, due to its severe effects on quality of life and its socioeconomic consequences. This study aimed to identify pandemic-related problems experienced by psoriasis patients followed up in our outpatient clinic, thereby revealing the effects of the COVID-19 pandemic on these patients. Materials and Methods: This study included 64 patients with plaque psoriasis who were followed up at the Psoriasis Outpatient Clinic of Aydın Adnan Menderes University Faculty of Medicine, Department of Dermatology 6 months before and after the start of the pandemic in Turkey. A questionnaire was used to inquire how the patients were affected by the pandemic; median Psoriasis Area and Severity Index (PASI) scores and number of hospital visits were compared with pre-pandemic values. Results: Thirty-six patients (56.3%) stated that the pandemic had no effect on their disease, 20 patients (31.3%) reported a deterioration of their disease. The most common reasons thought to aggravate disease were pandemic-related stress and changes in treatment regimen. Treatment of 43 patients (67.2%) remained the same during the pandemic. There was a change in treatment in 21 patients (32.8%). The median number of patient visits to our outpatient clinic was 3 before the pandemic, which dropped to 2 during the first 6 months of the pandemic (p<0.001). PASI scores were compared on an individual basis, and 30 patients (46.9%) in the study group had an increase in their median PASI scores during the pandemic. Conclusion: The COVID-19 pandemic led to fewer patient visits to the hospital and difficulties in managing patient compliance to treatment. Our study showed that approximately half the psoriatic patients being treated had an increase in the severity of their disease during the COVID-19 pandemic. A considerable percentage of these patients linked this deterioration with the pandemic.